Fruit and Vegetable Consumption and the Incidence of Hypertension in Three Prospective Cohort Studies. Issue 2 (February 2016) - Borgi, Lea; Muraki, Isao; Satija, Ambika; Willett, Walter C.; Rimm, Eric B.; Forman, John P.
Abstract : Increased fruit and vegetable intake lowers blood pressure in short-term interventional studies. However, data on the association of long-term intake of fruits and vegetables with hypertension risk are scarce. We prospectively examined the independent association of whole fruit (excluding juices) and vegetable intake, as well as the change in consumption of whole fruits and vegetables, with incident hypertension in 3 large longitudinal cohort studies: Nurses' Health Study (n=62 175), Nurses' Health Study II (n=88 475), and Health Professionals Follow-up Study (n=36 803). We calculated hazard ratios and 95% confidence intervals for fruit and vegetable consumption while controlling for hypertension risk factors. Compared with participants whose consumption was ⩽4 servings/week, the pooled hazard ratios among those whose intake was ≥4 servings/day were 0.92(0.87–0.97) for total whole fruit intake and 0.95(0.86–1.04) for total vegetable intake. Similarly, compared with participants who did not increase their fruit or vegetable consumption, the pooled hazard ratios for those whose intake increased by ≥7 servings/week were 0.94(0.90–0.97) for total whole fruit intake and 0.98(0.94–1.01) for total vegetable. Analyses of individual fruits and vegetables yielded different results. Consumption levels of ≥4 servings/week (as opposed to <1 serving/month) of broccoli, carrots, tofu or soybeans, raisins, and apples was associated with lower hypertension risk. In conclusion, our results suggest that greater long-term intake and increased consumption of whole fruits may reduce the risk of developing hypertension. Abstract : Supplemental Digital Content is available in the text.